Sodium-dependent phosphate cotransporter type 1 sequence polymorphisms in male patients with gout. Issue 6 (24th June 2009) - Urano, Wako; Taniguchi, Atsuo; Anzai, Naohiko; Inoue, Eisuke; Kanai, Yoshikatsu; Yamanaka, Mariko; Endou, Hitoshi; Kamatani, Naoyuki; Yamanaka, Hisashi
Abstract : Objectives: Molecular biological approaches have recently identified urate transporters in renal proximal tubular cells. Human sodium-dependent phosphate cotransporter type 1 encoded by SLC17A1 is a urate transporter localised to the renal proximal tubular cells and candidate molecule to secret urate from renal tubular cells to urine. This study investigated the roles of SLC17A1 in the development of gout. Patients and Methods: Single nucleotide polymorphisms in the human SLC17A1 gene (rs1165176, rs1165151, rs1165153, rs1165196, rs1165209, rs1165215, rs1179086, rs3799344 and rs3757131) were selected, and an association study was conducted using male patients with gout (n=175) and male controls (n=595). Results: There were significant differences between gout and control groups in the distribution of genotypes at rs1165196 (T806C; Ile269Thr, odds ratio (OR) 0.55, p=0.0035), rs1179086 (OR 0.57, p=0.0018) and rs3757131 (OR 0.54, p=0.0026). In controls, T806C alone had no effect on serum uric acid (sUA) levels. However, T806C showed significant interaction with a reduction of sUA in obese individuals (body mass index ≥25) using multiple regression analysis. Conclusions: Our data suggest that SLC17A1 polymorphisms are associated with the development of gout.